A compact short-wave receiving antenna for use in high-noise areas - Muggleton, Louis Miles (Department of Electrical Engineering, 2016)
An antenna has been developed with a signal-to-noise performance that is better than that of a typical Rhombic antenna during local thunder storms. Although the design is of general application to the reception, in high-noise areas, of long distance transmissions, this work deals in particular with the London-Salisbury circuit, at September noon, 1956, on 21.47 Mc/s. A basis of theoretical comparison between the performances of different antennas has been proposed. It relies on the technique of replacing a thunder storm by an "equivalent radio transmitter" set up on the frequency to which the receiver is tuned and for which the antenna is designed. A V.H.F. scale model has been used to produce an optimum design for the proposed antenna which is an end-fire array of parasitic elements. The polar diagrams and signal-to-noise performance of the proposed design are derived for several different types of earth mat. The method used for these derivations is substantiated by correlation with practical sampling measurements. A specification for the final configuration is given and its applicability is indicated by applying the design to the problem of improving the expected performance on the London-Salisbury transmissions from September to December, 1960.